The triangular seed mass–leaf area relationship holds for annual plants and is determined by habitat productivity. (15th May 2017) - Santini, Bianca A.; Hodgson, John G.; Thompson, Ken; Wilson, Peter J.; Band, Stuart R.; Jones, Glynis; Charles, Mike; Bogaard, Amy; Palmer, Carol; Rees, Mark
Summary: Plant allometries help us to understand resource allocation in plants and provide insight into how communities are structured. For woody species, a triangular allometric relationship between seed size and leaf size occurs in which all combinations are all possible, except for species with big seeds and small leaves (Cornelissen 1999 ). This relationship is thought to be a consequence of between‐habitat variation in abiotic conditions. In this study, we tested if the triangular relationship between seed mass and leaf area holds for annual species, and if variation in soil productivity and light (measured as Ellenberg indicator values: EIVs) is driving this relationship. We show that the triangular relationship also holds for annuals, which suggests that the allometric combinations between leaf area and seed mass are conserved across life‐forms. The triangular relationship was driven by between habitat variation in soil productivity. This means that as soil productivity increases, plants with bigger leaves could have either big or small seeds. However, in low soil productivity habitats, plants are constrained in their options, and plants with small leaves can only have small seeds. A lay summary is available for this article. Abstract : Lay Summary